THE EFFECTIVENESS OF RED BEANS MODISCO ICE CREAM AND MORINGA OLEIFERA MODISCO ICE CREAM TO INCREASE BODY WEIGHT OF TODDLERS UNDER THE RED LINE IN KARANGANYAR PUBLIC HEALTH CENTER PEKALONGAN REGENCY - Hidayah, Nur; Aulia, Dhita; Nugraheni, Intan (Postgraduate Program , Poltekkes Kemenkes Semarang, 2020)
Every year more than one-third of child deaths in the world are related to malnutrition. Children with malnutrition tend to have slow physical and mental growth. Pekalongan is one of the regencies in Central Java which is included in the top 10 categories of malnutrition cases (ranked 5) with 49 cases. Karanganyar Public Health Center is one of the health centers which has toddlers under the red line and the highest malnutrition cases in Pekalongan Regency.The purpose of this research was to know the difference of the effectiveness of red beans modisco ice cream and Moringa Oleifera modisco ice cream in regard of increasing body weight of toddlers under the red line in Karanganyar Public Health Center, Pekalongan.This research used pre experimental design with one group pretest posttest design. The writer used purposive sampling technique that resulted in 28 toddlers under the red line; 14 toddlers were given red bean modisco ice cream and 14 others were given Moringa Oleifera modisco ice cream. Red beans modisco ice cream and Moringa Oleifera modisco ice cream were given for 14 days as much as 100 gr. A daily monitoring checklist of modisco ice cream given to toddlers was used as the instrument of this research.The results of this research showed that the difference body weight pre- post given red bean modisco ice cream (0,21%), while in moringa oleifera modisco ice cream (0,56%). Based on Mann Whitney test showed that moringa oleifera modisco ice cream more effective to increased the body weight of toddlers with p value 0,000 (p value <0.05). According to the results, parents and community were able to modify additional foods which made from modisco and moringa oleifera to increased the body weight of toddlers.